Blended Learning in a Paragraph Writing Course: A Case Study - Anggri Muhtia; Suparno Suparno; Sumardi Sumardi (International Journal of Language Teaching and Education, 2018)
The emergence of online learning offers the opportunities that are not possessed by the traditional face-to-face learning environment. Combining the strengths of the online learning and face-to-face learning, known as blended learning, is believed to enhance the quality of learning. Different subjects may have different designs of blended learning because there is no specific formula for the best practices of blended learning. This paper reports a study investigating the implementation of blended learning in a paragraph writing course. The purposes were to investigate the blended learning activities carried out in the paragraph writing course and to find out the extent to which it affected students’ writing paragraph performance. The participants of this case study, who were selected purposively, involved one lecturer and six students of a paragraph writing class. The techniques for collecting data included interviews, observations, and document analysis, and the data were analyzed using Miles and Huberman’s interactive model. Ten blended learning activities, including five activities in face-to-face settings and five activities online, were identified in the course. The students’ paragraph writing performance seen from the result of final test was satisfying, indicating that the use of blended learning had a positive effect on students’ writing performance.